2019
DOI: 10.1097/txd.0000000000000947
|View full text |Cite
|
Sign up to set email alerts
|

Incidentally Detected Malignancies in Lung Transplant Explants

Abstract: Background.Active malignancy diagnosed within 5 years is an absolute contraindication for lung transplantation. In this study, we evaluated the rate of incidental malignancies detected in explanted lungs at our institution and assessed the posttransplant survival in patients with nonsmall cell lung cancer (NSCLC).Methods.A retrospective chart review of lung transplant recipients at our institution from February 1999 to June 2017 was conducted. A literature review was performed to evaluate the prevalence and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This may be attributed to the fact that the pooled data have publication bias, which is defined as the failure to publish the results of research based on the direction or strength of study outcomes [ 18 ]. Therefore, based on the assumption that OPTN data are closer to the real-world data, the 3-year overall survival after DLT for lung cancer was almost 5–10 times higher than that of previously known stage IV lung cancer and 5–8 times higher than that of non-localized lung cancers [ 19 21 ]. Furthermore, the causes of death were varying, and we found that cancer-related deaths were only 33% in the OPTN data [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be attributed to the fact that the pooled data have publication bias, which is defined as the failure to publish the results of research based on the direction or strength of study outcomes [ 18 ]. Therefore, based on the assumption that OPTN data are closer to the real-world data, the 3-year overall survival after DLT for lung cancer was almost 5–10 times higher than that of previously known stage IV lung cancer and 5–8 times higher than that of non-localized lung cancers [ 19 21 ]. Furthermore, the causes of death were varying, and we found that cancer-related deaths were only 33% in the OPTN data [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a consensus document for the selection of lung transplant candidates recommended that lung cancer may be a special consideration in cases of AIS or MIA of histological type and refractory to conventional medical treatments or those associated with respiratory failure [ 12 ], only 0.1% of lung transplantations have been performed for lung cancer during the last 2 decades [ 2 ]. However, the incidence of unexpected malignancy found in removed lungs after lung transplantation is approximately 2.2%, which is higher than the incidence of lung cancer as a primary indication for lung transplantation [ 21 ]. These findings indicate that the practice of excluding patients with a lung cancer diagnosis from lung transplantation should be reassessed.…”
Section: Discussionmentioning
confidence: 99%